2005
DOI: 10.1038/sj.ejcn.1602295
|View full text |Cite
|
Sign up to set email alerts
|

Zinc status and taste acuity in older Europeans: the ZENITH study

Abstract: Background: Age-related decline in taste acuity may be both a cause and an effect of depleted zinc and/or increased zinc requirement. Objective: The aim of this study was to explore associations between zinc status and taste acuity in healthy older European adults aged 55-90 y. Sample: Volunteers were recruited within Italy (n ¼ 108 aged 70-90 y), the United Kingdom (UK) (n ¼ 93 aged 55-70) and two regions of France (n ¼ 186), Grenoble (aged 70-90 y) and Clermont-Ferrand (aged 55-70 y). Methods: A signal detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…emotion was correctly identified) and 'false alarms', following the 3-AFC Signal Detection procedure (see Frijters, 1979 for discussion; also Dessirier & Mahoney, 1998;Stewart-Knox et al, 2005;Stillman, 1993). Descriptive data detailing performance before the stimulation manipulation can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…emotion was correctly identified) and 'false alarms', following the 3-AFC Signal Detection procedure (see Frijters, 1979 for discussion; also Dessirier & Mahoney, 1998;Stewart-Knox et al, 2005;Stillman, 1993). Descriptive data detailing performance before the stimulation manipulation can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…22 In this study the presence of xerostomy, taste dysfunction, nausea and vomiting were observed in both groups, but with less intensity in group B. All these symptoms may have affected food choices and are factors directly related to weight changes in children with leukemia.…”
Section: Discussionmentioning
confidence: 84%
“…24 It is also possible that the mineral can be rapidly redistributed among other tissues in response to metabolic needs or retained in liver for accelerated protein synthesis, in the form of zinc-thymulin and other complexes. 25 As for the management of mucositis, there have been many studies dedicated to its prevention and treatment 22,26,27 including zinc supplementation. As zinc is a substantial element for collagen synthesis, for fibroblast and keratinocyte proliferation, it is expected to enhance the re-epithelialization rate in wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…However, the best results were obtained when zinc is supplemented at the doses recommended by RDA as zinc gluconate or aspartate or acetate, less when zinc was used as zinc sulphate (Haase and Rink 2009b). No effects on cellmediated and humoral immunity were observed when zinc was used at high doses and as zinc sulphate (90 mg/day for 3-6 months) (Provinciali et al 1998b;Stewart-Knox et al 2005). Anyway, improvements upon the immune system in general occur with however many limitations.…”
Section: Potential Usefulness Of Zn Supplementation In Elderly Subjectsmentioning
confidence: 97%
“…Clinical evidences support the pathological consequences that can occur during zinc deficiency that is a serious public health problem from young up to old age (Table 1). Such a deficiency in ageing is typically the result of an inadequate zinc dietary intake that may occur as a response to reduced energy requirements or age-related sensory impairment (Stewart-Knox et al 2005). It has been reported that mild zinc deficiency is a significant clinical problem in free-living elderly people: only 42.9% have a sufficient intake of zinc (defined as >67% of the recommended daily allowance (RDA)) (Prasad et al 1993).…”
Section: Dietary Zinc Deficienciesmentioning
confidence: 99%